Synthesis and characterization of new Co(II), Rh(III), and Pt(II) guanidine and thiourea complexes - Da, Weihao; Jones, T. Harri; Lin, J.-B.; Blight, Barry A. (Canadian journal of chemistry, 2023)
Guanidine- and thiourea-based complexes have been the subject of extensive study due to their wide range of potential applications, including but not limited to anti-cancer drugs, ion transporters, and sensors. Building upon previous work done in this group, we aimed to demonstrate a new series of organometallic complexes based on functionally diverse guanidine and thiourea ligands. Herein, the synthesis and characterization of new platinum, rhodium, and cobalt complexes is presented. While most of these complexes conformed to properties and behaviours in line with previous work, one complex based on a Pt(II) and guanidine derivative exhibited unusual supramolecular properties, demonstrating a larger self-assembled dimer consisting of six Pt(II) cations.